Association of the −243A>G, +61450C>A Polymorphisms of the Glutamate Decarboxylase 2 (GAD2) Gene with Obesity and Insu¬lin Level in North Indian Population - Jai PRAKASH; Balraj MITTAL; Shally AWASTHI; Neena SRIVASTAVA (Tehran University of Medical Sciences, 2016)
Background: Obesity associated with type 2 diabetes, and hypertension increased mortality and morbidity. Glutamate decarboxylase 2 (GAD2) gene is associated with obesity and it regulate food intake and insulin level. We investigated the association of GAD-2gene −243A>G (rs2236418) and +61450C>A (rs992990) polymorphisms with obesity and related phenotypes. Methods: Insulin, glucose and lipid levels were estimated using standard protocols. All subjects were genotyped (PCR-RFLP) method. Results: The −243A>G polymorphism of the GAD-2 gene was significantly associated with higher risk of obesity (P<0.05). Conclusion: GAD-2 gene polymorphisms influence obesity and related phenotype in complex manner, probably by regulating the food intake, insulin and body weight.   Keywords: Obesity, Insulin, GAD-2, Food intake, Polymorphism